Crack initiation in the brittle fracture of ferritic steels - Coates, M; Kumar, A; Roberts, S (2006)
Fracture in many steels is thought to initiate from fractured carbides. It is often supposed that in pre-cracked specimens, many carbides fracture in the plastic zone of the pre-crack, and that eventually fracture propagates from one of these to cause fracture of the whole specimen. Sources of fracture initiation in steels were investigated using a modified A533B steel as a model material. Specimens were annealed to produce a distribution of micron-sized carbides in a ferrite matrix. Four-point bend tests were carried out in the temperature range 77-373K to determine the material's ductile brittle transition. Pre-cracked samples were loaded up to 90% of the fracture strength at temperatures on the lower shelf (163K) and at the mid point of the transition region (243K). The samples were then sectioned and polished to produce SEM and TEM samples containing the crack tip. Other samples were made of areas some distance from the crack tip and out of the plastic zone. An extensive search for fracture initiation sites found no evidence for fracture initiation originating from fractured carbides. © 2006 Blackwell Publishing Ltd.